Challenging scenarios in nontuberculous mycobacterial infection in cystic fibrosis. Issue 2 (10th December 2019) - Martiniano, Stacey L.; Esther, Charles R.; Haworth, Charles S.; Kasperbauer, Shannon H.; Zemanick, Edith T.; Caverly, Lindsay J.
Abstract: This review summarizes the discussion of a session held during the 2018 North American Cystic Fibrosis (CF) Conference titled "Challenging Cases in Nontuberculous Mycobacterial (NTM) Management." In this session, a multidisciplinary panel of NTM experts discussed clinical challenges related to the management of NTM infection in people with CF in which decision‐making falls outside of the Cystic Fibrosis Foundation/European Cystic Fibrosis Society NTM guidelines. Topics discussed included managing newly acquired NTM infection, selecting and monitoring treatment regimens, determining treatment endpoints, and caring for patients after NTM treatment.